Realtrack: Real-time tracking system for construction site progress / Syahirah Mat Sahizol Raduan - Mat Sahizol Raduan, Syahirah (2022)
Construction site progress tracking is essential in providing the overall construction site progress tracking in which innovation needs to be immersed. Therefore, an innovation in real-time tracking systems, which is the RealTrack system has been proposed, mainly to facilitate the current conventional tracking method, which is paper-based, obtained data not digitally stored, inaccurate data attainment, and time consuming. The RealTrack system functioning by an observer such as a project manager, needs to be either on-site or off-site, using the Radio Frequency Identification (RFID) controller to control the drone with the RFID scanner to scan the RFID tags on the structural elements. Later the scanned data will be transferred to a data bank. The data will be processed in the scheduling software using the 4D Building Information Modelling (4D BIM) and the integration of project planning software before it is ready for reporting, which results in real-time data. This innovation is an improvisation of the conventional tracking method by assisting the project manager to track the numerous constructions progresses, tracking project ahead or delay days more easily, and provide digital data from the construction site that is more accurate in faster way and improve the communication among the construction project team.